Danos cromossômicos e apoptose em células esfoliadas do epitélio bucal associados ao hábito de fumar e ás lesões pré-malignas e malignas do epitélio oral - Dórea, Lavínia Tércia Magalhães (2008)
The cancer is considered a genetic disease once it results from alterations in genes involved with DNA repair or in genes controlling the cellular proliferation and differentiation. The oral cancer is preceded by precursor stages that induce some changes in cells of oral epithelium. The biomarkers uses are essential for monitoring of premalignant lesions. Epidemiological studies have shown that oral cancer and premalignant lesions are associated with many factors, emphasizing tobacco smoking and alcohol drinking, mainly when in concomitance. The aim of this study was to evaluate through a differentiated protocol of the Micronucleus Test, the frequencies of micronuclei and degenerative nuclear alterations indicative of apoptosis, in exfoliated cells from oral epithelium of individuals presenting premalignant and malignant lesions of this epithelium and possible interaction with smoking habits. The analysed sample consisted of 20 individuals with oral cancer; 11 individuals with premalignant lesions and 72 individuals without oral lesions. Cells were obtained from normal and lesion areas of the cheek by scrapping with a cervical brush. Smears were stained according to Feulgen/ Fast Green. Analysis was performed under light microscopy in a blind fashion in a minimum of 1,000 cells. The frequency of micronucleus was significantly higher in individuals with oral lesions (cells obtained from lesions area), as compared with the frequency observed in individuals without oral lesions and in normal area cells of individuals with lesions (p<0.00001). The frequency of micronucleus was significantly higher between women; between smokers and mouthwashes use. A significant stepwise increase in the frequency of micronuclei was observed in buccal epithelium exfoliated cells, from individuals without lesions to individuals with cancer. Considering the obtained in normal area cells of individuals with lesions e without lesions were not detected differences significant. The frequency of apoptosis was significantly lower in the individuals with oral lesions (as considering lesions exfoliated cells or normal exfoliated cells mucosa) than observed individuals without lesions (P<0.0001). These results show that: 1) the process of malignant transformation involves an increase in the frequency of chromosomal damage and the loss of cell ability in evolving to apoptosis; 2) the components of tobacco are effective to induce micronucleus.